Kevlar fiber reinforced current collector-based structural electrode, preparation method and structural battery

By using structural electrodes based on Kevlar fiber reinforced current collectors in structural batteries, the shortcomings in existing structural batteries in terms of mechanical properties and specific energy are solved, and structural batteries with high mechanical strength and high specific energy are achieved.

CN119764460AActive Publication Date: 2025-04-04CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411866282.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-04
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing structural batteries have shortcomings in terms of mechanical properties and specific energy. Traditional battery cells do not have load-bearing capacity. Multifunctional composite structural batteries have not yet met the comprehensive performance requirements for practical applications.

Method used

Using a structural electrode based on Kevlar fiber reinforced current collector, a layer of electrode material with high mechanical strength is constructed by deposition of modified Kevlar fiber layer and conductive metal, and mechanical coupling between the packaging shell and the structural electrode is achieved through a special packaging method.

Benefits of technology

The mechanical strength and cyclic stability of structural electrodes are improved, the high specific energy and mechanical properties of structural batteries are improved, and the weight and space occupied are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764460A_ABST
    Figure CN119764460A_ABST
Patent Text Reader

Abstract

The invention provides a structural electrode based on a Kevlar fiber reinforced current collector, a preparation method and a structural battery, the structural electrode comprises the Kevlar fiber reinforced current collector and an electrode material layer arranged on the surface of the Kevlar fiber reinforced current collector, the Kevlar fiber reinforced current collector is a modified Kevlar fiber layer modified with conductive metal, the modified Kevlar fiber layer is obtained by modifying Kevlar fibers through trimethylchlorosilane. The Kevlar fiber reinforced current collector has higher mechanical strength than a traditional metal foil current collector, so that the mechanical strength of the structural electrode prepared by adopting the current collector is improved, the structural electrode can effectively relieve volume expansion and stress accumulation, the battery is ensured to have high specific energy, and meanwhile, the service life of the battery is prolonged. The cycling stability is improved; the structural battery provided by the invention adopts an integrated continuous packaging mode, and through mechanical coupling of the packaging shell and the structural electrode, continuous load transmission between the internal battery cell and the external package is realized, and the mechanical property of the structural battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of structural batteries, and in particular to a structural electrode based on a Kevlar fiber reinforced current collector, a preparation method and a structural battery. Background Art

[0002] Structural energy storage batteries are developed as the requirements for weight reduction, structure and service life of electrical equipment continue to increase. They are used to achieve the dual purpose of weight reduction and extended service life while maintaining structural performance. In engineering structures, structural batteries can be used as both structural elements and energy storage units, thereby reducing the volume / mass of the entire system, solving the most basic size and weight problems of batteries, and improving the potential for system efficiency.

[0003] In the civilian field, structural batteries can be used in consumer electronics such as smartphones and laptops, and small electric devices such as electric bicycles, which can reduce weight while making the structure more compact. In addition, the application of structural batteries in transportation equipment such as electric vehicles and drones is very important. When structural batteries become part of the structure of cars and drones and withstand impact and torsional loads, they can reduce the fastening process and additional structural reinforcement brought by the use of traditional power battery packs, thereby reducing the occupied space, reducing weight, and increasing the range.

[0004] At present, the main types of structural batteries are: embedded integrated structural batteries with composite shells and structural components, multifunctional composite structural batteries with composite structural material layers and energy storage material layers, etc. However, embedded integrated structural batteries use traditional cells, which do not have any carrying capacity. Multifunctional composite structural batteries are far from practical applications in terms of comprehensive performance, and their overall specific energy is at a very low level. Summary of the invention

[0005] The object of the present invention is to provide a structured electrode, a preparation method and a structured battery based on a Kevlar fiber reinforced current collector to solve the problems in the background technology.

[0006] The technical solution of the present invention includes: a structural electrode based on a Kevlar fiber reinforced current collector, which includes a Kevlar fiber reinforced current collector and an electrode material layer arranged on the surface thereof, wherein the Kevlar fiber reinforced current collector is a modified Kevlar fiber layer modified with a conductive metal.

[0007] Furthermore, the modified Kevlar fiber layer is obtained by modifying Kevlar fiber with trimethylchlorosilane.

[0008] Furthermore, the conductive metal is at least one of copper and aluminum.

[0009] Furthermore, the electrode material layer is a positive electrode material layer or a negative electrode material layer, and the positive electrode material layer includes a nano positive electrode active material, a conductive agent and a binder, and the nano positive electrode active material includes LiNi x Co y Al 1-x-y O2、LiNi x Co y Mn 1-x-y At least one of O2, LiMPO4 (M=Fe, Mn) and LiCoO2, and the negative electrode material layer is a pressure-diffused lithium belt or a evaporated lithium layer.

[0010] The technical solution of the present invention also includes: a method for preparing the structured electrode based on Kevlar fiber reinforced current collector as described above, which comprises the steps of:

[0011] The Kevlar fiber is immersed in a modification solution containing trimethylchlorosilane, and after modification, it is washed and dried to obtain a modified Kevlar fiber layer;

[0012] Depositing a conductive metal on the modified Kevlar fiber layer to obtain a Kevlar fiber reinforced current collector;

[0013] The electrode material layer is placed on the portion of the Kevlar fiber reinforced current collector where the conductive metal is deposited to obtain a structured electrode.

[0014] Furthermore, the method used for depositing the conductive metal is electrochemical deposition, with a current density of 80 to 120 mA / cm 2 , the deposition time is 10 to 40 minutes.

[0015] Furthermore, the method of placing the electrode material layer on the Kevlar fiber reinforced current collector is a slurry coating method, a pressure infiltration method or a vapor deposition method.

[0016] The technical solution of the present invention also includes: a structural battery, which includes a packaging shell, a positive electrode, a negative electrode and a separator impregnated with a structural electrolyte, wherein the positive electrode and the negative electrode respectively adopt the structural electrodes based on Kevlar fiber reinforced current collectors described in claims 1-4.

[0017] Furthermore, the Kevlar fiber reinforced current collector in the positive electrode includes a positive electrode material area and a first annular area surrounded by the outside thereof; the Kevlar fiber reinforced current collector in the negative electrode includes a negative electrode material area and a second annular area surrounded by the outside thereof; the diaphragm includes a structural electrolyte infiltration area and a third annular area surrounded by the outside thereof; the first annular area and the second annular area are respectively fixedly connected to the two sides of the third annular area; the packaging shell is respectively arranged on the separated sides of the positive electrode and the negative electrode, and is fixedly connected to the Kevlar fiber reinforced current collector in the positive electrode or the negative electrode.

[0018] Furthermore, the packaging shell, the positive electrode, the negative electrode and the separator are fixedly connected by an epoxy resin-curing agent layer, the epoxy resin-curing agent layer comprises an epoxy resin and a curing agent, the epoxy resin is any one of EP-301, EP-360, EP-365, E-44, E-51, E-54, E-57, E-58, EP-1001, YD-128, ER2221 and EP828AB, and the curing agent is any one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, phthalic anhydride, linoleic acid dimer and eleostearic acid dimer.

[0019] The beneficial effects of the present invention include at least:

[0020] (1) Kevlar fiber reinforced current collector has higher mechanical strength than traditional metal foil current collector, thus improving the mechanical strength of the structured electrode prepared by using this current collector;

[0021] (2) The structural electrode based on Kevlar fiber reinforced current collector can effectively alleviate volume expansion and stress accumulation, ensuring that the battery has high specific energy while improving cycle stability;

[0022] (3) The structural electrode based on Kevlar fiber reinforced current collector is applied to the structural battery, and a special packaging method is adopted to realize the mechanical coupling between the packaging shell and the structural electrode, thereby realizing the continuous transfer of load between the internal battery cell and the external packaging, thereby improving the mechanical properties of the structural battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of a structural battery in an embodiment of the present invention.

[0024] In the figure:

[0025] 1. Package shell;

[0026] 2. structural positive electrode; 21. positive electrode material layer; 22. first annular region;

[0027] 3. structural negative electrode; 31. negative electrode material layer; 32. second annular region;

[0028] 4. Diaphragm; 41. Electrolyte wetting area; 42. Third annular area. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with embodiments and drawings:

[0030] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and comparative examples, and are not intended to limit the scope of protection of the present invention. It should be particularly noted that there may be multiple names for the same organic structure, as long as the structure is within the scope of this patent, it belongs to the protection object of this patent.

[0031] Unless otherwise defined, the raw materials, reagents, etc. in the following examples can be purchased from the market or prepared according to reported methods.

[0032] Reference Figure 1 The first aspect of the present invention provides a structural electrode based on a Kevlar fiber reinforced current collector and a preparation method thereof. The structural electrode can be a positive electrode or a negative electrode. In the present embodiment, it specifically includes a Kevlar fiber reinforced current collector and an electrode material layer arranged on the surface of the Kevlar fiber reinforced current collector. Therefore, the electrode material layer can be a positive electrode material layer 21 or a negative electrode material layer. Kevlar fiber has high mechanical strength, so it can replace the current collector layer in a conventional battery to improve the structural strength of the structural electrode in the present invention, and then improve the structural strength of the structural battery containing the structural electrode. However, Kevlar fiber itself does not have the ability to conduct electrons, and conductive metals need to be deposited or grown on its surface. In order to improve the bonding ability and bonding strength between the conductive metal and the Kevlar fiber, the Kevlar fiber needs to be surface modified to improve its surface activity. Therefore, the Kevlar fiber reinforced current collector selected in the present invention is a modified Kevlar fiber layer modified with a conductive metal, and the modified Kevlar fiber layer is obtained by modifying the Kevlar fiber by trimethylchlorosilane.

[0033] Different conductive metals can be selected according to the types of structural electrodes to be prepared. The conductive metal can be copper or aluminum.

[0034] The specific methods for modifying and modifying conductive metals are as follows:

[0035] (1) immersing Kevlar fiber in a modification solution containing trimethylchlorosilane, and washing and drying after modification to obtain a modified Kevlar fiber layer;

[0036] In this step, the solvent in the modified solution can be selected from different organic solvents according to actual needs. For example, in this embodiment, dichloromethane is used as the solvent, and trimethylchlorosilane in the modified solution is used as a modifying agent to activate the surface of the Kevlar fiber, thereby improving its surface activity, allowing the conductive metal to be evenly deposited on the surface of the Kevlar fiber and enhancing the bonding strength with the Kevlar fiber, thereby improving the stability of the electronic conduction ability of the Kevlar fiber reinforced current collector when used as a current collector, and achieving uniform distribution of current during battery charging and discharging.

[0037] In this step, when the Kevlar fiber is modified by immersing it in a modification solution containing trimethylchlorosilane, the mixture is firstly ultrasonically mixed, infiltrated, and soaked, and then the mixture is kept warm in a water bath at 30 to 50° C. and stirred for 0.5 to 12 hours. After the water bath, the mixture is allowed to stand at room temperature for 30 minutes, and after being repeatedly washed with ethanol for 3 to 5 times, the modified Kevlar fiber layer is placed in a vacuum drying oven to dry overnight, so that the residual reagent on its surface can be fully volatilized.

[0038] To ensure the mechanical strength of the Kevlar fiber-enhanced current collector, the Kevlar fiber should be selected from Kevlar fiber fabrics with a thickness of 5 to 50 μm. To reduce the weight of the battery, the woven surface density of the modified Kevlar fiber layer should be controlled so that its surface density (including the deposited conductive metal) is less than that of the conventional metal foil current collector.

[0039] (2) depositing a conductive metal on the modified Kevlar fiber layer to obtain a Kevlar fiber reinforced current collector;

[0040] In this step, the method for depositing the conductive metal can be selected according to actual needs. For example, the present embodiment adopts the electrochemical deposition method. During the electrochemical deposition, the cathode electrode is obtained by covering a modified Kevlar fiber layer on a graphite plate, the anode electrode adopts an inert conductive material (existing technology), the cathode electrolyte is an aqueous solution containing copper ions or aluminum ions, wherein the concentration range of the copper ions or aluminum ions is 0.1 to 1.0 mol / L, the anode electrolyte is an aqueous solution containing low-valent vanadium ions or divalent iron ions, and a DC power supply is used, and the current density is 80 to 120 mA / cm 2 , the deposition time is 10 to 40 minutes.

[0041] After electrochemical deposition, the Kevlar fiber reinforced current collector needs to be soaked and cleaned with clean water for 2 to 3 times, or cleaned with clean water for 1 to 2 minutes using a circulating pump.

[0042] After obtaining the Kevlar fiber reinforced current collector, the structured electrode can be prepared. The specific method is: using a slurry coating method, a pressure infiltration method or a vapor deposition method, the electrode material layer is placed on the portion where the conductive metal is deposited on the Kevlar fiber reinforced current collector to obtain a structured electrode.

[0043] The positive electrode material layer 21 includes nano-positive electrode active materials, conductive agents and binders. The nano-positive electrode active materials include LiNi x Co y Al 1-x-y O2、LiNi x Co y Mn 1-x-yAt least one of O2, LiMPO4 (M=Fe, Mn) and LiCoO2, with a particle size of 20 to 1000nm. The conductive agent and the adhesive are both existing technologies in this field and can be selected according to needs. No more specific restrictions are made here. The positive electrode material layer 21 can be constructed by a slurry coating method on the part where the conductive metal is constructed on the Kevlar fiber reinforced current collector.

[0044] The above-mentioned negative electrode material layer 31 can be a pressure-diffused lithium belt or a vapor-deposited lithium layer. As the name implies, the pressure-diffused lithium belt is to place the lithium belt on the part where the conductive metal is arranged on the Kevlar fiber reinforced current collector, and squeeze the lithium belt through a hydraulic press to make the lithium belt penetrate into the Kevlar fiber reinforced current collector. The pressure range of the hydraulic press is 1 to 50 MPa, and the pressing is 1 to 8 hours. The vapor-deposited lithium layer is to place lithium metal in a vapor deposition machine, vapor-deposit metallic lithium on the part where the conductive metal is arranged on the Kevlar fiber reinforced current collector, and then place it on a rolling machine for compaction. The temperature range of the vapor deposition machine is 300 to 400°C, the vapor deposition is 0.5 to 6 hours, the servo parameters of the rolling machine are 10 to 100 μm, and the rolling speed is 10 to 100 mm / min.

[0045] The structural electrode based on Kevlar fiber reinforced current collector provided in this embodiment can improve the structural strength of the structural electrode itself and improve its structural stability when impacted, because Kevlar fiber itself has excellent mechanical strength and toughness, and Kevlar fiber has good plastic deformation ability, which can release the accumulated internal stress and resist volume change during battery charging and discharging. In addition, the resin-based structural electrolyte commonly used in structural batteries can produce mechanical-electrochemical coupling with the Kevlar fiber reinforced current collector, effectively inhibiting the formation of lithium dendrites and alleviating battery volume expansion and stress accumulation.

[0046] The second aspect of the present invention provides a structural battery, which includes a packaging shell, a positive electrode 2, a negative electrode 3 and a separator 4 impregnated with a structural electrolyte. The positive electrode 2 and the negative electrode 3 in the structural battery of this embodiment respectively adopt the structural electrode based on Kevlar fiber reinforced current collector described in the first aspect above.

[0047] In order to improve the impact resistance of the structural battery, in this embodiment, the Kevlar fiber reinforced current collector in the positive electrode 2 is configured to include a positive electrode material area and a first annular area 22 surrounded by the outside thereof, and the positive electrode material layer 21 is configured only in the positive electrode material area; the Kevlar fiber reinforced current collector in the negative electrode 3 is configured to include a negative electrode material area and a second annular area 32 surrounded by the outside thereof, and the negative electrode material layer 31 is configured only in the negative electrode material area; the diaphragm 4 is configured to include a structural electrolyte impregnation area 41 and a third annular area 42 surrounded by the outside thereof, and the structural electrolyte is impregnated only in the electrolyte impregnation area 41; the first annular area and the second annular area are respectively fixedly connected to the two sides of the third annular area; the packaging shell is respectively arranged on the separated sides of the positive electrode 2 and the negative electrode 3, and the Kevlar fiber reinforced current collector in the positive electrode 2 or the negative electrode 3 is fixedly connected.

[0048] By fixing the first annular area, the second annular area, the third annular area and the packaging shell, the internal and external integrity of the structural battery is achieved, and the continuous transmission of loads between the internal battery cell and the external packaging is achieved, so as to avoid interlayer slippage of the structural layers of the internal battery cell caused by external force impact on the structural battery, and improve the mechanical properties of the structural battery through mechanical coupling between the packaging shell and the structural electrode based on Kevlar fiber reinforced current collector.

[0049] In the above technical solution, the diaphragm 4 can be a glass fiber diaphragm.

[0050] In the above technical scheme, the packaging shell 1, the positive electrode 2, the negative electrode 3 and the separator 4 are fixed by an epoxy resin-curing agent layer, the epoxy resin-curing agent layer includes an epoxy resin and a curing agent, the epoxy resin is any one of EP-301, EP-360, EP-365, E-44, E-51, E-54, E-57, E-58, EP-1001, YD-128, ER2221 and EP828AB, and the curing agent is any one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, phthalic anhydride, linoleic acid dimer and tungoleic acid dimer. The mass ratio of epoxy resin to curing agent is 100:33. The mixture is brushed on the first annular area 22, the second annular area 32, the third annular area 42 and the Kevlar fiber reinforced current collector on the side where the positive electrode 2 and the negative electrode 3 are separated, and stacked in the order of packaging shell 1-positive electrode 2-diaphragm 4-negative electrode 3-packaging shell 1. It is cured and formed by vacuum heating at a heating condition of 50-120°C and allowed to stand for 24-48 hours after heating.

[0051] Compared with the prior art, the beneficial effects of the present invention include at least:

[0052] Some specific embodiments and comparative examples are disclosed below.

[0053] Example 1

[0054] The structured negative electrode based on Kevlar fiber reinforced current collector is prepared as follows:

[0055] (1) immersing Kevlar fiber in a modification solution containing trimethylchlorosilane, and washing and drying after modification to obtain a modified Kevlar fiber layer;

[0056] In this step, Kevlar fiber is selected from Kevlar fiber plain fabric with a thickness of 50 μm, and the solvent in the modification solution is dichloromethane. When the Kevlar fiber is immersed in the modification solution containing trimethylchlorosilane for modification, the mixture is firstly ultrasonically mixed, infiltrated, and soaked for 3 hours, and then the mixture is kept warm in a 40°C water bath and stirred for 1 hour. After the water bath, it is allowed to stand at room temperature for 30 minutes, and after repeated washing with ethanol for 3 times, the modified Kevlar fiber layer is placed in a vacuum drying oven for 8 hours at a drying temperature of 100°C to fully volatilize the residual reagents on its surface.

[0057] (2) depositing a conductive metal on the modified Kevlar fiber layer to obtain a Kevlar fiber reinforced current collector;

[0058] In this step, the method for depositing the conductive metal can be an electrochemical deposition method. During the electrochemical deposition, the cathode electrode is obtained by covering a modified Kevlar fiber layer on a graphite plate, the anode electrode is made of an inert conductive material, the cathode electrolyte is a cupric chloride aqueous solution, the anode electrolyte is a ferrous chloride aqueous solution, a DC power supply is used, and the current density is 100 mA / cm 2 , the deposition time is 30min.

[0059] After the electrochemical deposition, the Kevlar fiber reinforced current collector was soaked and cleaned with clean water for three times, and then dried in a forced air drying oven at 60°C.

[0060] (3) Using the pressure infiltration method, the negative electrode material layer 31 is placed on the portion of the Kevlar fiber reinforced current collector where the conductive metal is deposited to obtain a structural negative electrode.

[0061] In this step, the negative electrode material layer 31 uses a 20μm thick lithium ribbon, which is placed on the part of the Kevlar fiber reinforced current collector where the conductive metal is placed. The lithium ribbon is squeezed by a hydraulic press to make the lithium ribbon penetrate into the Kevlar fiber reinforced current collector. The pressure range of the hydraulic press is 4MPa, and the pressing is performed for 1h.

[0062] Example 2

[0063] The structured negative electrode based on Kevlar fiber reinforced current collector is prepared as follows:

[0064] (1) immersing Kevlar fiber in a modification solution containing trimethylchlorosilane, and washing and drying after modification to obtain a modified Kevlar fiber layer;

[0065] In this step, Kevlar fiber is selected from Kevlar fiber plain fabric with a thickness of 50 μm, and the solvent in the modification solution is dichloromethane. When the Kevlar fiber is immersed in the modification solution containing trimethylchlorosilane for modification, the mixture is firstly ultrasonically mixed, infiltrated, and soaked for 3 hours, and then the mixture is kept in a 35°C water bath and stirred for 2 hours. After the water bath, it is allowed to stand at room temperature for 30 minutes, and after repeated washing with ethanol for 3 times, the modified Kevlar fiber layer is placed in a vacuum drying oven for 8 hours at a drying temperature of 100°C to fully volatilize the residual reagents on its surface.

[0066] (2) depositing a conductive metal on the modified Kevlar fiber layer to obtain a Kevlar fiber reinforced current collector;

[0067] In this step, the method for depositing the conductive metal can be an electrochemical deposition method. During the electrochemical deposition, the cathode electrode is obtained by covering a modified Kevlar fiber layer on a graphite plate, the anode electrode is made of an inert conductive material, the cathode electrolyte is a cupric chloride aqueous solution, the anode electrolyte is a ferrous chloride aqueous solution, a DC power supply is used, and the current density is 100 mA / cm 2 , the deposition time is 30min.

[0068] After the electrochemical deposition, the Kevlar fiber reinforced current collector was soaked and cleaned with clean water for three times, and then dried in a forced air drying oven at 60°C.

[0069] (3) Using the evaporation method, the negative electrode material layer structure 31 is placed on the portion of the Kevlar fiber reinforced current collector where the conductive metal is deposited to obtain a structural negative electrode.

[0070] In this step, lithium metal is placed in a vapor deposition machine, and metallic lithium is vapor-deposited on the portion of the Kevlar fiber reinforced current collector where a conductive metal is arranged, and then it is placed on a rolling machine for compaction. The temperature range of the vapor deposition machine is 350°C, the vapor deposition is performed for 1 hour, the servo parameters of the rolling machine are 60μm, and the rolling speed is 20mm / min.

[0071] Example 3

[0072] The process of preparing a structural positive electrode based on a Kevlar fiber reinforced current collector is as follows:

[0073] (1) immersing Kevlar fiber in a modification solution containing trimethylchlorosilane, and washing and drying after modification to obtain a modified Kevlar fiber layer;

[0074] In this step, Kevlar fiber is selected from Kevlar fiber plain fabric with a thickness of 30 μm, and the solvent in the modification solution is dichloromethane. When the Kevlar fiber is immersed in the modification solution containing trimethylchlorosilane for modification, the mixture is firstly ultrasonically mixed, infiltrated, and soaked for 3 hours, and then the mixture is kept in a 45°C water bath and stirred for 0.5 hours. After the water bath, it is allowed to stand at room temperature for 30 minutes, and after repeated washing with ethanol for 3 times, the modified Kevlar fiber layer is placed in a vacuum drying oven for 8 hours at a drying temperature of 100°C to fully volatilize the residual reagents on its surface.

[0075] (2) depositing a conductive metal on the modified Kevlar fiber layer to obtain a Kevlar fiber reinforced current collector;

[0076] In this step, the method for depositing the conductive metal can be an electrochemical deposition method. During the electrochemical deposition, the cathode electrode is obtained by covering a modified Kevlar fiber layer on a graphite plate, the anode electrode is an inert conductive material, the cathode electrolyte is an aluminum chloride aqueous solution, the anode electrolyte is a ferrous chloride aqueous solution, a DC power supply is used, and the current density is 80 mA / cm 2 , the deposition time is 20min.

[0077] After the electrochemical deposition, the Kevlar fiber reinforced current collector was soaked and cleaned with clean water for three times, and then dried in a forced air drying oven at 60°C.

[0078] (3) The positive electrode material layer 21 is formed on the portion of the Kevlar fiber reinforced current collector where the conductive metal is deposited by using a slurry coating method to obtain a structural positive electrode.

[0079] In this step, the positive electrode material layer 21 includes a nano positive electrode active material, a conductive agent and a binder. The nano positive electrode active material is selected from LiNi 0.8 Co 0.1 Al 0.1 O2, the conductive agent is SuperP, and the adhesive is 6wt% polyvinylidene fluoride-hexafluoropropylene. The three are mixed in a mass ratio of 90:5:5, and a proper amount of NMP is added to dilute it. After stirring, the mixture is evenly coated on the Kevlar fiber reinforced current collector, and the structural positive electrode is obtained after drying and rolling.

[0080] Example 4

[0081] Preparation of structural batteries

[0082] The structured negative electrode prepared in Example 1 and the structured positive electrode prepared in Example 3 were assembled as follows:

[0083] A mixture of epoxy resin and curing agent is applied to the second annular area 32 of the structural negative electrode, the first annular area 22 of the structural positive electrode, the third annular area 42 of the glass fiber separator, and the separated sides of the structural positive electrode and the structural negative electrode respectively; the aluminum-plastic film, the structural negative electrode, the separator impregnated with the structural electrolyte, the structural positive electrode, and the aluminum-plastic film are stacked in sequence, and vacuum heated and cured at 80°C for 36 hours to obtain a structural battery.

[0084] In this embodiment, the mixture of epoxy resin and curing agent contains epoxy resin E-51 and phthalic anhydride curing agent, and the mass ratio of the two is 100:33.

[0085] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A structural electrode based on a Kevlar fiber reinforced current collector, characterized in that: The invention comprises a Kevlar fiber reinforced current collector and an electrode material layer arranged on the surface thereof. The Kevlar fiber reinforced current collector is a modified Kevlar fiber layer modified with a conductive metal.

2. The structured electrode based on Kevlar fiber reinforced current collector according to claim 1, characterized in that: The modified Kevlar fiber layer is obtained by modifying Kevlar fiber with trimethylchlorosilane.

3. The structured electrode based on Kevlar fiber reinforced current collector according to claim 1 or 2, characterized in that: The conductive metal is at least one of copper and aluminum.

4. The structure electrode based on Kevlar fiber reinforced current collector according to claim 3, characterized in that: The electrode material layer is a positive electrode material layer or a negative electrode material layer, and the positive electrode material layer includes a nano positive electrode active material, a conductive agent and a binder. The nano positive electrode active material includes LiNi x Co y Al 1-x-y O2、LiNi x Co y Mn 1-x-y At least one of O2, LiMPO4 (M=Fe, Mn) and LiCoO2, and the negative electrode material layer is a pressure-diffused lithium belt or a evaporated lithium layer.

5. A method for preparing a structured electrode based on a Kevlar fiber reinforced current collector according to any one of claims 1 to 4, characterized in that: Includes steps: The Kevlar fiber is immersed in a modification solution containing trimethylchlorosilane, and after modification, it is washed and dried to obtain a modified Kevlar fiber layer; Depositing a conductive metal on the modified Kevlar fiber layer to obtain a Kevlar fiber reinforced current collector; The electrode material layer is placed on the portion of the Kevlar fiber reinforced current collector where the conductive metal is deposited to obtain a structured electrode.

6. The method for preparing a structured electrode based on a Kevlar fiber reinforced current collector according to claim 5, characterized in that: The method used to deposit the conductive metal is electrochemical deposition with a current density of 80 to 120 mA / cm 2 , the deposition time is 10 to 40 minutes.

7. The method for preparing a structured electrode based on a Kevlar fiber reinforced current collector according to claim 5, characterized in that: The method of placing the electrode material layer on the Kevlar fiber reinforced current collector is a slurry coating method, a pressure infiltration method or a vapor deposition method.

8. A structural battery, characterized in that: The invention comprises a packaging shell, a positive electrode, a negative electrode and a diaphragm impregnated with a structural electrolyte, wherein the positive electrode and the negative electrode respectively adopt the structural electrode based on Kevlar fiber reinforced current collector as described in claims 1-4.

9. The structural battery according to claim 8, characterized in that: The Kevlar fiber reinforced current collector in the positive electrode comprises a positive electrode material area and a first annular area arranged outside the positive electrode material area; The Kevlar fiber reinforced current collector in the negative electrode includes a negative electrode material area and a second annular area arranged outside the negative electrode material area; The diaphragm includes a structural electrolyte wetting area and a third annular area arranged outside the structural electrolyte wetting area. The first annular area and the second annular area are fixedly connected to two sides of the third annular area respectively and correspondingly; The packaging shells are respectively arranged on the separated sides of the positive electrode and the negative electrode, and are fixedly connected to the Kevlar fiber reinforced current collector in the positive electrode or the negative electrode.

10. The structural battery according to claim 9, characterized in that: The packaging shell, the positive electrode, the negative electrode and the separator are fixedly connected by an epoxy resin-curing agent layer, the epoxy resin-curing agent layer comprises an epoxy resin and a curing agent, the epoxy resin is any one of EP-301, EP-360, EP-365, E-44, E-51, E-54, E-57, E-58, EP-1001, YD-128, ER2221 and EP828AB, and the curing agent is any one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, phthalic anhydride, linoleic acid dimer and eleostearic acid dimer.

Citation Information

Patent Citations

  • Modified three-dimensional woven mesh current collector, modification method thereof and lithium ion battery

    CN111916758A

  • Surface-modified Kevlar fiber as well as preparation method and application thereof

    CN113789659A

  • Current collector, pole piece, battery monomer, battery, device, manufacturing method and equipment

    CN117378064A

  • High-strength positive electrode graphene composite fiber, preparation method and prepared structural battery

    CN117448987A

  • Flexible battery capable of freely designing shape and preparation method thereof

    CN118645704A